OPTIMASI MULTIRESPON PADA PROSES EDM SINKING BAJA ST 42 DENGAN MENGGUNAKAN METODE TAGUCHI DAN FUZZY LOGIC - Galang Sandy Prayogo; Nuraini Lusi; Dian Ridlo Pamuji (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2016)
The optimization technique of machining parameters considering multiple performance characteristics of non conventional machining EDM process using Taguchi method combined with fuzzy logic is presented in this study. ST 42 steel was chosen as material workpiece and graphite as electrode during this experiment. Performance characteristics such as material removal rate and overcut are selected to evaluated the effect of machining parameters. Current, pulse on time, pulse off time and discharging time/ Z down were selected as machining parameters. The experiments was conducted by varying that maching parameters in three different levels. Based on the Taguchi quality design concept, a L27 orthogonal array table was chosen for the experiments. By using the combination of fuzzy logic and Taguchi, the optimization of complicated multiple performance characteristics was transformed into the optimization of a single response performance index. Optimal levels of machining parameters were identified by using fuzzy logic method. The statistical application of analysis of variance was used to determine the relatively significant machining parameters. The result of confirmation test indicted that the determined optimal combination of machining parameters effectively improve the performance characteristics of the machining EDM process on ST 42 steel. Keywords: EDM, Taguchi, Fuzzy logic